2021
DOI: 10.1523/jneurosci.2879-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Pupil Responses Are Modulated by Predictability of Auditory Sequences

Abstract: The brain is highly sensitive to auditory regularities. To appreciate the impact that the presence of predictability has on perception, we need to better understand how a predictable structure influences processing and attention. We recorded listeners' pupil responses to sequences of tones that followed either a predictable or unpredictable pattern, as the pupil can be used to implicitly tap into these different cognitive processes. We found that the pupil showed a smaller sustained diameter to predictable seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…The human auditory system exhibits a remarkable sensitivity to detect and learn statistical regularities in sound ( Saffran et al, 1999 ; Skerritt-Davis and Elhilali, 2018 ). This capacity has been corroborated in statistical learning paradigms using behavioral ( Barascud et al, 2016 ; Bianco et al, 2020 ), eye-tracking ( Milne et al, 2021 ; Zhao et al, 2019 ), and neuroimaging techniques ( Barascud et al, 2016 ; Moldwin et al, 2017 ; Pesnot Lerousseau and Schön, 2021 ). Furthermore, humans have extraordinary implicit memory for auditory patterns ( Agres et al, 2018 ; Bianco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…The human auditory system exhibits a remarkable sensitivity to detect and learn statistical regularities in sound ( Saffran et al, 1999 ; Skerritt-Davis and Elhilali, 2018 ). This capacity has been corroborated in statistical learning paradigms using behavioral ( Barascud et al, 2016 ; Bianco et al, 2020 ), eye-tracking ( Milne et al, 2021 ; Zhao et al, 2019 ), and neuroimaging techniques ( Barascud et al, 2016 ; Moldwin et al, 2017 ; Pesnot Lerousseau and Schön, 2021 ). Furthermore, humans have extraordinary implicit memory for auditory patterns ( Agres et al, 2018 ; Bianco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…The human auditory system exhibits a remarkable sensitivity to detect and learn statistical regularities in sound (Saffran et al, 1999;Skerritt-Davis & Elhilali, 2018). This capacity has been corroborated in statistical learning paradigms using behavioural (Barascud et al, 2016;Bianco et al, 2020), eye-tracking (Milne et al, 2021;Zhao et al, 2019), and neuroimaging techniques (Barascud et al, 2016;Moldwin et al, 2017;Pesnot Lerousseau & Schön, 2021). Furthermore, humans have extraordinary implicit memory for auditory patterns (Agres et al, 2018;Bianco et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Borghini and Hazan (2020) replicated this interaction of findings, and further demonstrated that the effect of semantic context was indeed limited to native listeners and did not extend to nonnative listeners, suggesting a difference in real-time processing effort rather than mere differences in success after a sentence was already spoken. The impact of predictability on real-time effort extends beyond speech as well; Milne et al (2021) observed reduction of pupil dilation at the onset of coherent structure in an auditory stimulus consisting of tone pips. Each of these studies demonstrates that pupillometry can be used to interpret whether effort is engaged more rapidly or slowly across time.…”
Section: Dilations During Listeningmentioning
confidence: 99%